The role of ductility in hydraulic fracturing: An experimental study - Feng, R.; Zhou, G.; Sarmadivaleh, Mohammad; Rezagholilou, Ali; Roshan, H. (2018)
Copyright © 2018 ARMA, American Rock Mechanics Association. Previous studies show that the effective fracture toughness will increase with the rise of rock ductility during the hydraulic fracture propagation. Higher pump horsepower is required for fracture propagation and stimulation volume will decrease extensively. However, such conclusion was mainly validated by numerical modeling and field observation with much fewer experimental investigations. Three different sample types of silica-rich, calcite-rich, and clay-rich with distinct ductility was made. Mineralogy and clay content have a profound effect on ductility. Mechanical properties and ductility were measured and compared using UCS, Brazilian, semicircular bending toughness, and hydraulic fracturing tests. Hydraulic fracturing tests were conducted on cube of 10cm on true triaxial stress condition. Also, scaling laws were applied to simulate the field-like viscosity dominated propagation condition. A direct relation between sample ductility and lag time (between the fracture initiation and breakdown) was observed (i.e. longer lag time for samples with higher ductility). In addition, it was shown that ductile samples have slower fracture propagation.